1995
DOI: 10.1161/01.atv.15.5.704
|View full text |Cite
|
Sign up to set email alerts
|

Generation, Characterization, and Histochemical Application of Monoclonal Antibodies Selectively Recognizing Oxidatively Modified ApoB-Containing Serum Lipoproteins

Abstract: To investigate either the role oxidized LDL plays in atherosclerosis or structural changes on the surface of oxidized LDL, monoclonal antibodies (mAbs) are an important tool. After immunizing mice with Cu(2+)-oxidized LDL (oxLDL) and fusion of splenocytes, hybridoma supernatants were screened and cloned. Two mAbs, OB/04 and OB/09 (IgG and IgM), were further characterized. In solid-phase fluorescence immunoassays and Western blot analysis both mAbs reacted with oxLDL, LDL oxidized by a free radical-generating a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
59
0
1

Year Published

1997
1997
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 77 publications
(64 citation statements)
references
References 44 publications
4
59
0
1
Order By: Relevance
“…27,55,56 Hammer et al 57 similarly showed cellular staining for ox-LDL in macrophage foam cells in one cryosection of human atherosclerotic tissue from the femoral artery in a case of advanced arterial occlusive disease. In rabbit studies by Haberland et al 13 and Boyd et al, 12 monoclonal antibodies against MDA-LDL were used to demonstrate extracellular deposition of MDA-LDL adducts in early lesions.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…27,55,56 Hammer et al 57 similarly showed cellular staining for ox-LDL in macrophage foam cells in one cryosection of human atherosclerotic tissue from the femoral artery in a case of advanced arterial occlusive disease. In rabbit studies by Haberland et al 13 and Boyd et al, 12 monoclonal antibodies against MDA-LDL were used to demonstrate extracellular deposition of MDA-LDL adducts in early lesions.…”
Section: Discussionmentioning
confidence: 98%
“…Immunohistochemical analyses of atherosclerotic lesions have been performed on rabbit and human tissues. 12,13,27,[55][56][57] Additionally, there is one study on focal glomerulosclerotic lesions in the rat. 58 In considering the available data, it is important to heed two questions.…”
Section: Discussionmentioning
confidence: 99%
“…For Ox-LDL loading experiments, cells were seeded at a density of 1 ϫ 10 6 /ml in medium containing PMA (Research Biochemical International, Natick, MA) at 1 ϫ 10 Ϫ7 M for 24 h. The medium was then replaced by culture medium with or without 100 g/ml CuSO 4 "fully" oxidized LDL (Intracel, Rockville, MD) according to the method of Hammer et al (16). Medium was replaced every 2 days during the time of culture.…”
Section: Methodsmentioning
confidence: 99%
“…7 Oxidative modification of LDL induces immunogenic epitopes in the LDL molecule, 8 thus leading to formation of antibodies against oxLDL (oxLDLAbs) that are detectable in sera in the majority of patients with advanced atherosclerotic lesions 9 and can be measured as a tool for investigating the mechanisms of atherogenesis. 10 Several studies demonstrated an increased titer of oxLDLAbs in patients with atherosclerotic coronary artery disease (CAD), 9,[11][12][13] acute myocardial infarction (MI), 14 and cerebral or peripheral artery disease. 15,16 In contrast, other studies found no such positive relationship between oxLDLAb titers and cardiovascular (CV) phenotypes.…”
mentioning
confidence: 99%